Epically earnest - Horan, Molly (Clarion Books, an imprint of HarperCollinsPublishers, 2022)
"Jane Worthing's claim to fame is that she was one of the first viral internet sensations...discovered as a one-year-old in an oversized Gucci bag by her adopted father in a Poughkeepsie train station. Now in her senior year of high school, Janey is questioning whether she wants to look for her bio family due to a loving, but deeply misguided push from her best friend Algie, while also navigating an all-consuming crush on his cousin, the beautiful, way-out-of-her-league Gwen Fairfax"--Provided by publisher.